EXPLORING IRONY WITHIN PRAGMATIC MEANING FRAMEWORKS - Turdimatova Madinakhon Ravshanbek kizi (International Journal of Literature and Language Studies, 2026)
Irony is a complex and multifaceted phenomenon in language use, particularly within the field of pragmatics. This study explores how irony functions as a mechanism for conveying implicit meanings beyond literal interpretation. Drawing on pragmatic theories, including Gricean implicature and relevance theory, the paper examines how speakers use irony to express attitudes, criticism, and humor. The research adopts a qualitative approach, analyzing examples of ironic utterances in natural discourse. The findings suggest that irony plays a significant role in shaping pragmatic meaning and requires both contextual awareness and shared knowledge between interlocutors. The study highlights the importance of irony in communication and its implications for language teaching and comprehension.